1979
DOI: 10.1039/f19797502143
|View full text |Cite
|
Sign up to set email alerts
|

Study of the interaction of nitric oxide with Cu(100) and Cu(111) surfaces using low energy electron diffraction and electron spectroscopy

Abstract: The adsorption of nitric oxide on Cu(lO0) and Cu(l11) surfaces has been studied by combining X-ray and U.V. photoelectron spectroscopy with low energy electron diffraction. At 80K two molecular states, characterised by N(1s) values of 399.5 and 401 eV, have been assigned to '' bent " and " linear " configurations, respectively, The bent form dissociates slowly at 80 K while the h e a r species desorbs above z 170 K. Assignments of the " bent " and " linear " forms were facilitated by recourse to the known ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(34 citation statements)
references
References 2 publications
3
31
0
Order By: Relevance
“…For both cases, the dissociation proceeds in which the O atom is detached from the N atom and moves to the next fcc hollow site. It was experimentally identified that adsorbed NO on bent structure is the precursor for dissociation and agrees with the dissociation geometry obtained in our work 27) . In all stages, the distance between the N and O atoms is larger if it is on Cu _ Cu2O(111) than on Cu(111).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…For both cases, the dissociation proceeds in which the O atom is detached from the N atom and moves to the next fcc hollow site. It was experimentally identified that adsorbed NO on bent structure is the precursor for dissociation and agrees with the dissociation geometry obtained in our work 27) . In all stages, the distance between the N and O atoms is larger if it is on Cu _ Cu2O(111) than on Cu(111).…”
Section: Resultssupporting
confidence: 77%
“…By combining X-ray and UV photoelectron spectroscopy with low energy electron diffraction (LEED), Johnson et al found that adsorbed NO on Cu(111) in a bent configuration dissociated slowly at 80 K while the linearly adsorbed molecule desorbed upon heating the crystal at 170 K 27) . Nonetheless, it was not concluded whether the bent or linear structure was the initial adsorption structure but it was specified that the bent structure as precursor for NO dissociation.…”
Section: This Work: In Search For Alternative Catalyst For No Dissocimentioning
confidence: 99%
“…In addition, the dissociation of CO and NO proceeds much easier on the more open Cu(100) surface than on the close-packed Cu(111) surface, in agreement with experiments that show a greater reactivity for more open surfaces toward NO dissociation. 16,17,50 Another interesting conclusion can be made by comparing the bridged and diagonal reaction paths on either surface. On Cu(111), it is clearly the diagonal reaction path that is energetically favored for all systems studied, since we could rule out the bridged pathway that is too short for bringing about the dissociation.…”
Section: Resultsmentioning
confidence: 99%
“…On Cu(111), the initial adsorption state of NO at T ≈ 100 K was reported to be a monomeric species. [26][27][28][29][30][31][32] The bonding geometry was initially proposed to be a bent structure on the bridge site, based on comparison with the N-O stretching frequency of nitrosyl complexes. [26][27][28] However, the use of the vibrational frequency as a guide to determining the bonding site of NO on a metal surface was questioned, 33 and an upright NO molecule on the threefold site was proposed as a candidate for the adsorption structure on Cu(111).…”
Section: Introductionmentioning
confidence: 99%